Language Contact, Colonial Administration, and the Construction of Identity in Ancient Israel : Constructing the Context for Contact - Boyd, Samuel L. (Harvard Semitic Monographs., 2021)
"In Language Contact, Colonial Administration, and the Construction of Identity in Ancient Israel, Boyd addresses a long-standing critical issue in biblical scholarship: how does the production of the Bible relate to its larger historical, linguistic, and cultural settings in the ancient Near East? Using theoretical advances in the study of language contact, he examines in detail the sociolinguistic landscape during the Assyrian, Babylonian, and Achaemenid periods. Boyd then places the language and literature of Ezekiel and Isaiah in this sociolinguistic landscape. Language Contact, Colonial Administration, and the Construction of Identity in Ancient Israel offers the first book-length incorporation of language contact theory with data from the Bible. As a result, it allows for a reexamination of the nature of contact between biblical authors and a series of Mesopotamian empires beginning with Assyria."--